2017
DOI: 10.1002/2016ms000842
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of modeled land‐atmosphere exchanges with a comprehensive water isotope fractionation scheme in version 4 of the Community Land Model

Abstract: All physical process models and field observations are inherently imperfect, so there is a need to both (1) obtain measurements capable of constraining quantities of interest and (2) develop frameworks for assessment in which the desired processes and their uncertainties may be characterized. Incorporation of stable water isotopes into land surface schemes offers a complimentary approach to constrain hydrological processes such as evapotranspiration, and yields acute insight into the hydrological and biogeoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 59 publications
(95 reference statements)
0
69
1
Order By: Relevance
“…The deuterium excess, d‐excess (defined d‐excess = δD − 8 × δ 18 O), values are not simulated well, with less correlation with the observations and too large a mean (median bias = 3.3‰). The magnitude of this bias is similar to that found in previous works with prescribed ocean and sea ice values (Nusbaumer et al, ; Wong et al, ). This implies that these particular biases are products of the atmosphere and land‐surface components alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deuterium excess, d‐excess (defined d‐excess = δD − 8 × δ 18 O), values are not simulated well, with less correlation with the observations and too large a mean (median bias = 3.3‰). The magnitude of this bias is similar to that found in previous works with prescribed ocean and sea ice values (Nusbaumer et al, ; Wong et al, ). This implies that these particular biases are products of the atmosphere and land‐surface components alone.…”
Section: Resultsmentioning
confidence: 99%
“…iCESM1 is shown to capture the broad qualitative features of precipitation isotopic patterns, albeit with a low bias in δ 18 O values of precipitation. The representation of δ 18 O is more accurate than that of d‐excess, whose values are too low over land and do not correlate as well with observations, consistent with stand‐alone simulations in iCAM5 and iCLM4 (Nusbaumer et al, ; Wong et al, ). This result highlights the importance of continued refinement of the simulated hydrological cycle associated with clouds and terrestrial processes.…”
Section: Discussionmentioning
confidence: 99%
“…The stable water isotope tracer‐enabled version of iCESM1.2 includes water isotopes of oxygen and hydrogen in all the dynamically coupled model components. Studies show that iCESM1.2 compares favorably with other isotope‐enabled Earth system models of similar complexity (Nusbaumer et al, ; T. E. Wong et al, ). Likewise, a preindustrial iCESM simulation shows generally good agreement with observed spatial patterns of δ 18 O p and precipitation in and around the SASM region (Figures S1 and S2).…”
Section: Methodsmentioning
confidence: 97%
“…Likewise, a preindustrial iCESM simulation shows generally good agreement with observed spatial patterns of δ 18 O p and precipitation in and around the SASM region (Figures S1 and S2). We direct the reader to the following studies for additional details about the strengths and weaknesses of the water isotope‐enabled components: atmosphere (Nusbaumer et al, ), land (T. E. Wong et al, ), ocean (Zhang et al, ), and coupled system (Zhu et al, ). For this study, we focus on oxygen isotopic responses.…”
Section: Methodsmentioning
confidence: 99%
“…The water isotope-enabled Community Earth System Model (iCESM) version 1.3 is a state-of-the-art fully coupled Earth system model with the capability to simulate the oxygen isotopes in the hydrological cycle Wong et al, 2017;Zhang et al, 2017;Zhu, Liu, Brady, Otto-Bliesner, Marcott et al, 2017). The numerical experiments analyzed here are from a recent study .…”
Section: Methodsmentioning
confidence: 99%